Test audialny jako element humanistycznej edukacji gimnazjalistów - Bachura, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
When pondering on education we are constantly faced with the following issue - what is the basic aim of education in Polish studies? If we accept a statement that the said aim consists in reconstructing and promoting culture from one generation to the next we have to realize what a difficult task today’s school has to tackle. School is namely forced to act against development trends of the contemporary world. The aim of my article is to expand on the phenomenon of a radio sound text in the school education in Polish studies, as well as to present comments of secondary school pupils concerning that medium. Classes that I have held so far, the fact that 1 enabled my pupils to familiarize themselves with quality radio texts and their enthusiastic reaction, as well as willingness to participate in the so-called radio classes proves to me that it would be useful to introduce such classes at schools. 1 believe that the radio is able to successfully compete with the ubiquitous TV since forms that it offers prove to be attractive even to a very young listener.